Neonatal scrub typhus - A sepsis mimic - Jagruthi Reddy; Nishanth Rajan; Sridevi Dinakaran; Lalitha Krishnan (Wolters Kluwer Medknow Publications, 2021)
Background: Scrub typhus is the most prevalent rickettsial infection in India. It is caused by Orientia tsutsugamushi. Although there are few reports suggesting vertical transmission from the mother to baby, it is extremely rare. Clinical Description: We describe a 1-day-old baby who was referred to us for respiratory distress and diagnosed as meconium aspiration syndrome, the clinical features of which resolved by the 10th day. The baby developed fever on the 11th day of life and was detected to have developed pallor and hepatosplenomegaly. History revealed maternal fever preceding and continuing well beyond delivery. Management: Late-onset sepsis was initially suspected in the baby. After reviewing the maternal history, transplacental transmission of scrub typhus was considered. Immunoglobulin M enzyme-linked immunosorbent assay was positive in the mother-baby dyad, but polymerase chain reaction for scrub typhus was negative. However, both exhibited a dramatic response in resolution of fever with doxycycline in the former and clarithromycin in the latter. On follow-up, the baby was well and gaining weight. Conclusion: Proper history and early initiation of management are important for reducing the morbidity and mortality of newborns with scrub typhus.